Embedding Pt‐SnO Nanoparticles into MIL‐101(Cr) Pores: Hydrogen Production with Low Carbon Monoxide Content from a New Methanol Steam Reforming Catalyst. Issue 20 (27th May 2019) - Kamyar, Niloofar; Khani, Yasin; Amini, Mostafa M.; Bahadoran, Farzad; Safari, Nasser
Abstract: The catalyst Pt‐SnO@MIL‐101(Cr) was prepared using the cis ‐PtCl(SMe2 )2 (SnCl3 ) complex as a single precursor and characterized by inductively coupled plasma optical emission spectroscopy, (ICP‐OES), X‐ray powder diffraction (XRD), BET surface area analysis (SBET ), X‐ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM), field‐emission scanning electron microscopy (FE‐SEM), and temperature program reduction (TPR). A new complex, cis ‐PtCl(SMe2 )2 (SnCl3 ), was synthesized from the reaction of PtCl2 (SMe2 )2 with SnCl2 and characterized by thermogravimetric analysis (TGA), ICP‐OES, and 1 H NMR spectroscopy and used as the source of metals for preparation of the catalysts. The fabricated catalyst, Pt‐SnO@MIL‐101(Cr), with 10.2%, 19.7%, and 28.9% platinum loadings were used in a steam reforming of methanol (MSR) reaction using a microstructure monolith reactor in the temperature range of 150–300 °C. A high methanol conversion with a good selectivity of H2 and low CO selectivity was achieved in light of the stability of the catalyst with a small amount of coke formation in the monolith system. Abstract : The methanol steam reforming reaction was studied using Pt‐SnO@MIL‐101(Cr) as a catalyst in a monolith reactor in the temperature range of 150–300 °C. A catalyst was prepared from MIL‐101(Cr) and cis‐PtCl(SMe2 )2 (SnCl3 ) complex as a single precursor for loading of Pt‐SnO in MOF. A high methanol conversion with a good selectivity of H2, low selectivity of CO and low level of coke formation was achieved.